LES LIMITES A L’APPLICABILITE DES BAUX A LOYER A USAGE PROFESSIONNEL EN REPUBLIQUE DEMOCRATIQUE DU CONGO. - lupapa, moses kalombo; Ndala Clovis, masumbuko (IJRDO - Journal of Business Management, 2023)
This study examines the limitations of the applicability of commercial leases in the Democratic Republic of Congo (DRC). It highlights obstacles related to the lack of transparency in commercial transactions, widespread corruption in real estate matters, and weaknesses in the judicial system. Proposed solutions include promoting transparency, strengthening the judicial system, and promoting a culture of respect for contracts. These measures can help optimize the applicability of commercial leases in the DRC.